Measurements of several atmospheric gases above the South Pole in December 1986 from high-resolution 3- to 4-micron solar spectra - Goldman, Aaron; Murcray, Frank J.; Murcray, Frank H.; Murcray, David G.; Rinsland, Curtis P. (1988)
This paper reports the quantitative analysis of absorption features of a number of atmospheric gases in 0.02/cm resolution 3- to 4-micron solar spectra recorded at the Amundsen-Scott South Pole Station. The measurements were obtained shortly after the austral spring ozone minimum and define, for the first time, the ambient levels of the species immediately following the breakup of the polar vortex. The retrieved total vertical column amounts in molecules per sq cm are: 2.4 + or - 0.4 x 10 to the 21st for H2(O-16), 4.5 + or - 0.5 x 10 to the 18th for H2(O-18), 3.9 + or - 0.4 x 10 to the 17th for HDO, 2.1 + or - 0.2 x 10 to the 19th for CH4, 5.1 + or - 0.5 x 10 to the 21st for CO2, 3.9 + or - 0.4 x 10 to the 18th for N2O, and 3.7 + or - 0.5 x 10 to the 15th for C2H6. Identification of (C-12)H3D absorption features and a search for H2CO absorption in the spectral data are also described.